The effectiveness of artificial intelligence applications in enhancing adaptive teaching skills: ChatGPT as a model (Journal of the College of Basic Education, 2025)
The research sought to evaluate the effectiveness of a training program that utilizes ChatGPT as an educational decision-making tool in developing adaptive teaching skills among first-cycle teachers in the city of Lattakia. Based on their weak digital competencies and their need to develop adaptive teaching skills, the research proposed a systematic training program that leverages the advantages of ChatGPT to enhance teachers' ability to analyze learner data, customize educational content, design and implement adaptive lessons, and adapt assessment methods. The quasi-experimental approach was followed with a single-group design. The performance of (30) teachers was measured before and after the intervention using a skill test and an observation card. The results showed statistically significant differences in favor of the post-intervention on both tools and across the four skills, confirming the program's effectiveness in improving teachers' skill performance and enhancing their adaptive teaching practices.In light of the statistical results, the study presented several proposals, including: expanding the scope of the program to include teachers at all educational levels, organizing practical workshops in classrooms to enhance actual practice, and conducting follow-up studies to measure the impact of adaptive teaching supported by artificial intelligence on student achievement and engagement.